Registro del Patrimonio Cultural Inmaterial de la Comunidad de Rumicruz (Calpi- Riobamba). - Mesache Manotoa, Jenny Maribel (2018)
The objective of this present investigation is to register the Intangible Cultural Heritage of the Rumicruz community, through the INPC records for later its delivery, there is a great variety of PCI that the inhabitants of the community practiced throughout their lives and that identifies them as people clearly cultural by their customs, traditions and ancestral knowledge. According to Mrs. Concha Buñay (personal communication, August 5, 2018), resident of the community, she tells that the great part of the community's customs and traditions are not preserved, this has been due to different factors such as adopting current fashions and one of the factors that effects in the worldwide and especially to this small community that is migration. For this reason, in order to recover this information, the interview technique was used, which was very important for the collection of information and the instruments used throughout the investigation were the questions established in the INPC records, this was done to 25 adult people of the community, who helped to know more about the intangible heritage that the people of the community of Rumicruz keep in their memory. The design of the research was qualitative, where it was possible to show the phenomena as they are presented to develop in their environment; the type of investigation that was used during the investigation was the field, since the place of the facts was used to understand and collect the respective information on the subject that is being investigated in the community, and thanks to this, it was possible to obtain a fruitful result that allowed reaching the respective conclusions.